ASSESSMENT OF QUALITY OF LIFE AND SOCIAL ADAPTATION IN VITILIGO PATIENTS - Rajapov M.Sh. (Modern American Journals, 2025)
Vitiligo is an autoimmune disease characterised by depigmented white patches on the skin. Nowadays it is increasingly emphasised that treating vitiligo purely as an aesthetic problem is a mistake. Various studies have shown that the disease negatively affects quality of life and social adaptation: patients face difficulties related to daily activities, work, education and psychosocial health[1]. Many patients experience depression, anxiety and low self‑esteem, forcing them to withdraw from social events[2]. This article analyses modern scientific sources on the quality of life and social adaptation of patients living with vitiligo and presents our own observational findings.
Keywords: vitiligo, quality of life, social adaptation, stigmatisation, depression, DLQI, VitiQoL.